Managing Social Responsibility Functional Strategies, Decisions and Practices - Turker, Duygu (CSR, Sustainability, Ethics & Governance,, 2018)
This book explores how business organizations incorporate socially responsible approaches into their diverse functional strategies, decisions, and practices. It analyzes the nature and dynamics of each function as well as their specific characteristics in the formulation of sustainable strategies and decisions. As such, the book comprehensively aligns recent approaches on social responsibility and sustainability with real-world practices. By viewing corporate social responsibility (CSR) as the catalyzer of United Nations' Sustainable Development Goals (SDGs) at the organizational level, this book introduces readers to the latest thinking and best practices towards the accomplishment of those overarching goals of humanity. Cases and examples from production, marketing, finance, accounting, human resources, and all parts of the enterprise make this book a valuable resource for scholars, students, up-and-coming managers and practitioners alike.